Implications of HIV Drug Resistance on First- and Second-Line Therapies in Resource-Limited Settings: Report from a Workshop Organized by the Collaborative HIV and Anti-HIV Drug Resistance Network. Issue 6 (August 2013) - Pillay, Deenan; Albert, Jan; Bertagnolio, Silvia; Boucher, Charles; Brun-Vezinet, Francoise; Clotet, Bonaventura; Giaquinto, Carlo; Perno, Carlo F
Here, we summarize the discussions and conclusions from an expert workshop held in October 2012 to consider the implications of HIV drug resistance in the context of scale-up of access to antiretroviral therapy and prophylaxis in resource-limited settings. Topics considered during the workshop included the implications of drug resistance for the selection of first-line regimens and sequencing of treatments, optimal surveillance strategies and prevention of mother-to-child transmission.